Targeting Salmonella Typhimurium Invasion and Intracellular Survival Using Pyrogallol - Birhanu, Biruk Tesfaye; Lee, Eon-Bee; Lee, Seung-Jin; Park, Seung-Chun (Frontiers in Microbiology, 2021)
Salmonella enterica serovar Typhimurium, an intracellular pathogen, evades the host immune response mechanisms to cause gastroenteritis in animals and humans. After invading the host cells, the bacteria proliferate in Salmonella-containing vacuole (SCV) and escapes from antimicrobial therapy. Moreover, Salmonella Typhimurium develops resistance to various antimicrobials including, fluoroquinolones. Treating intracellular bacteria and combating drug resistance is essential to limit the infection rate. One way of overcoming these challenges is through combination therapy. In this study, Pyrogallol (PG), a polyphenol, is combined with marbofloxacin (MAR) to investigate its effect on Salmonella Typhimurium invasion and intracellular survival inhibition. The Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of PG against Salmonella Typhimurium were 128 and 512 µg/mL, respectively. The lowest fractional inhibitory concentration (FIC) index for a combination of PG and MAR was 0.5. The gentamycin protection assay revealed that PG (30 µg/mL) alone and in combination with sub-MIC of MAR inhibited 72.75 and 76.18 % of the invading bacteria in Caco-2 cells, respectively. Besides, the intracellular survival of Salmonella Typhimurium was reduced by 7.69 and 74.36 % in treatment with PG alone and combined with sub-MIC of MAR, respectively, which was visualized by the confocal microscopy. PG has also shown to increase the intracellular accumulation of fluoroquinolone by 15.2 and 34.9 % at 30 and 100 30 µg/mL concentration, respectively. Quantitative real-time PCR demonstrated PG suppressed the genetic expression of hilA, invF, sipB, and acrA by 14.6, 15.4, 13.6, and 36 %, respectively. However, the downregulation of hilA, invF, sipB, and acrA increased to 80, 74.6, 78, and 70.1 %, in combination with sub-MIC of MAR, respectively. Similarly, PG combined with MAR inhibited the expression of sdiA, srgE, and rck genes by 78.6, 62.8, and 61.8 %, respectively. In conclusion, PG has shown antimicrobial activity against Salmonella Typhimurium alone and in combination with MAR. It also inhibited invasion and intracellular survival of the bacteria through downregulation of quorum sensing, invading virulence, and efflux pump genes. Hence, PG could be a potential antimicrobial candidate which could limit the intracellular survival and replication of Salmonella Typhimurium.